2017
DOI: 10.1007/s00520-017-3603-1
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of musculoskeletal impairment in head and neck cancer patients

Abstract: Musculoskeletal impairment is a significant side effect in head and neck cancer survivors that results in chronic neck pain, shoulder disability, trismus, and postural deficits. Tools to describe postural deficits are needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
30
0
5

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(41 citation statements)
references
References 33 publications
6
30
0
5
Order By: Relevance
“…This study has described key factors associated with neck disability, which have been identified as underreported in a recent systematic review [14]. Previous studies of patients with HNC have reported similar NDI scores to the present study, but were much smaller and not limited to a surgical population [50] [51]. In contrast, the NDI has been used extensively in the musculoskeletal neck pain literature [21] to measure self-reported neck disability.…”
Section: Discussionsupporting
confidence: 51%
“…This study has described key factors associated with neck disability, which have been identified as underreported in a recent systematic review [14]. Previous studies of patients with HNC have reported similar NDI scores to the present study, but were much smaller and not limited to a surgical population [50] [51]. In contrast, the NDI has been used extensively in the musculoskeletal neck pain literature [21] to measure self-reported neck disability.…”
Section: Discussionsupporting
confidence: 51%
“…The lower mean values of the sHNC compared to the control group for the cervical and shoulder AROM variables obtained in the present work agree with reductions consistently reported for populations with HNC (including sHNC) [5,16,18]. Extension and inclination to both sides on the cervical region were lower in sHNC.…”
Section: Plos Onesupporting
confidence: 91%
“…MMO was measured (mm) once as the inter-incisor distance (with the patient sitting) using a sliding caliper [17,18].…”
Section: Maximum Mouth Openingmentioning
confidence: 99%
See 1 more Smart Citation
“…19 Previous reviews have found objective and subjective patient reports of reduced MMO often correlate, however, some patients may continue to complain of trismus while having an MMO within the normal range. [20][21][22] The lack of uniform criteria contributes to the wide range of prevalence presented in previous studies. In addition to the lack of clear diagnostic criteria, there is limited evidence to support clinical guidelines for intervention and treatment.…”
mentioning
confidence: 99%